COPING STRATEGY OF WOMEN ANXIETY IN REGENCY PERIOD AS REFLECTED IN “PRIDE AND PREJUDICE” MOVIE - nensia nensia (Universitas Muhammadiyah Gorontalo, 2020)
This research aims to describe coping strategy of women anxiety in Regency period as it is reflected in the movie of Pride and Prejudice. The method used in this study was a descriptive qualitative. The primary data used were the dialogues in the movie “Pride and Prejudice”. The result of this study indicated that women in Regency period depicted in this literary work employed interesting coping strategies in their life where they deeply concerned about their future significantly money, higher social status, and marriage caused by anxiety.